1988
DOI: 10.1152/ajprenal.1988.254.6.f900
|View full text |Cite
|
Sign up to set email alerts
|

Renin and angiotensinogen gene expression and intrarenal renin distribution during ACE inhibition

Abstract: To define whether intrarenal renin and angiotensinogen synthesis and distribution are affected by angiotensin-converting enzyme (ACE) inhibition, a control group of adult, male Wistar-Kyoto rats (n = 7) was compared with a group of rats treated with enalapril (n = 8) for 5 days. Kidney renin and angiotensinogen mRNA levels were detected by Northern and dot blot analysis, using full-length rat renin and angiotensinogen cDNAs. Renin mRNA levels in the enalapril-treated group were 4.6-fold higher than in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
65
2
4

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(86 citation statements)
references
References 0 publications
15
65
2
4
Order By: Relevance
“…In adult mammals, low Na ϩ or RAS inhibition by angiotensin-converting enzyme (ACE) inhibitors, such as captopril, upregulate ren mRNA and renin protein (21,80). In combination, low salinity and captopril result in juxtaglomerular cell hypertrophy and renin cell recruitment along renal arterioles (7,18,36,67). Blockade of the RAS cascade arrests the ANG II-mediated negative feedback loop regulating ren transcription and renin cell recruitment (36).…”
Section: Larval Fish Renin Characterizationmentioning
confidence: 99%
“…In adult mammals, low Na ϩ or RAS inhibition by angiotensin-converting enzyme (ACE) inhibitors, such as captopril, upregulate ren mRNA and renin protein (21,80). In combination, low salinity and captopril result in juxtaglomerular cell hypertrophy and renin cell recruitment along renal arterioles (7,18,36,67). Blockade of the RAS cascade arrests the ANG II-mediated negative feedback loop regulating ren transcription and renin cell recruitment (36).…”
Section: Larval Fish Renin Characterizationmentioning
confidence: 99%
“…Renin is traditionally thought to be expressed in the juxtaglomerular apparatus (JGA) and secreted into blood vessels for its endocrine, exocrine, and paracrine functions. However, it has been shown that ACE inhibition increases the staining of renin by recruiting more cells farther along the afferent arterioles by the JGA (82). Further, recent data also identified renin expression along other parts of the nephron, such as the proximal tubules and collecting ducts (165).…”
Section: Nistala Et Al 2066mentioning
confidence: 99%
“…We have shown that renin precursor cells originate from the metanephric mesenchyme and give rise to JG cells, arteriolar smooth muscle cells (SMCs), mesangial cells, and a subset of proximal tubular cells (30,31). In adult animals, when homeostasis is threatened (such as by dehydration or hypotension) there is an increase in the number of renin-expressing cells along the renal arterioles and in the glomeruli and interstitium, resembling the fetal pattern, a phenomenon called recruitment (5,7). The process does not involve cell replication and/or migration (2), but it occurs by retransformation of arteriolar SMCs and mesangial cells into renin-expressing cells (30).…”
mentioning
confidence: 99%